2020
DOI: 10.3390/app10072455
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Laden Thermosensitive Chitosan Hydrogel Bioinks for 3D Bioprinting Applications

Abstract: Three-dimensional (3D) bioprinting is a technology used to deposit cell-laden biomaterials for the construction of complex tissues. Thermosensitive hydrogels are physically cross-linked by non-covalent interaction without using crosslinkers, facilitating low cytotoxicity and cell viability. Chitosan, which is a non-toxic, biocompatible and biodegradable polysaccharide, can be used as a thermosensitive hydrogel. Therefore, chitosan hydrogel could be of potential use as a 3D bioprinting ink. The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Adhikari et al [ 28 ] developed a CS/alginate 3D printable bioink reinforced with hydroxyapatite, combining both pre- and post-printing crosslinking. Moreover, some studies reported the use of a support frame, made from synthetic thermoplastic polymer, to improve the shape of the CS constructs [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adhikari et al [ 28 ] developed a CS/alginate 3D printable bioink reinforced with hydroxyapatite, combining both pre- and post-printing crosslinking. Moreover, some studies reported the use of a support frame, made from synthetic thermoplastic polymer, to improve the shape of the CS constructs [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The unreacted –NH 2 groups of chitosan for such hydrogels are responsible for the material’s response to environmental pH variation. More recently, hydrogels of chitosan [ 32 ] and starch [ 33 ] were prepared by dissolution/melt-blending in carboxylic acids (i.e., acetic and citric acids) for applications in 3D bio-printing. Formation of single-component starch-based hydrogels are known to involve gelatinization, followed by a retrogradation process to form a 3D network [ 34 ].…”
Section: Fabrication Of Bio-based Hydrogelsmentioning
confidence: 99%
“…Adapted with permission. [ 155 ] Copyright 2020, MDPI. G) The thermosensitive swelling of N‐isopropyl acrylamide (PNIPAAm) 3D‐printed hydrogel.…”
Section: Materials and Biomaterials For 3d‐printable Hydrogels For Bomentioning
confidence: 99%